Historiografi Ruang Kronologi Museum Dirgantara Mandala Yogyakarta - Imam Mashud (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
Museum is one of the institutions that store historical objects in the past which is intended to be exhibited to the general public. In general, the arrangement of exhibitions in museums is a part of the museum curator historiography who has its specific purpose. In addition, this study is intended to find out how the historiography is displayed in Museum Dirgantara Mandala Yogyakarta. Therefore, as an inductive reasoning study, it used methods of collecting data such as field observations, interviews and literature studies. In this case, observation and interviews are used to find out the primary data of this study. Finally, this study found that the historiography of the chronological room in Museum Dirgantara Mandala Yogyakarta is a part of nationalistic historiography, which its exhibition system mostly explained the greatness of the struggles events and the heroes itself.